2021
DOI: 10.1177/14624745211043543
|View full text |Cite
|
Sign up to set email alerts
|

The promises and pitfalls of path dependence frameworks for analyzing penal change

Abstract: Although the study of penal changes throughout history is central to punishment studies, the field has taken little from historical institutionalists’ theories of institutional change. One of the most relevant such theories is path dependence. This article outlines path dependence frameworks’ most fruitful elements for studying penal change. Drawing on foundational political science and historical sociology texts, as well as several punishment scholars’ works, this article highlights the advantages of thinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…And, conversely, striking continuities when path dependence prepared us to see change and innovation. Striving to reconcile the established value of path dependence for theorising stability and its rich promise for studies of punishment and criminal justice (Rubin, 2023) with its limitations for explaining our empirical case, we proposed a blended version of this framework in dialogue with recent theorising on palimpsestic penality (Quinn, Canossini & Evans, 2020). We suggested that outdoor penal labour in California is akin to a palimpsest -a blurry combination of practices, framings, and rhetorical justifications assembled and interpreted by skilled and variously motivated penal administrators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And, conversely, striking continuities when path dependence prepared us to see change and innovation. Striving to reconcile the established value of path dependence for theorising stability and its rich promise for studies of punishment and criminal justice (Rubin, 2023) with its limitations for explaining our empirical case, we proposed a blended version of this framework in dialogue with recent theorising on palimpsestic penality (Quinn, Canossini & Evans, 2020). We suggested that outdoor penal labour in California is akin to a palimpsest -a blurry combination of practices, framings, and rhetorical justifications assembled and interpreted by skilled and variously motivated penal administrators.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand this case, we weld together historical scholarship on path dependence with a recent foray into analogising punishment as palimpsestic (Quinn, Canossini & Evans, 2020). Following Rubin (2023), we see theories of path dependence as holding tremendous promise for studies of punishment – particularly as a way to sharpen focus on penal stability amid scholars’ arguably more acute attention to penal shifts, ruptures and change. Understandings of path dependence are useful, at the broadest level, because they acknowledge that history matters (Sewell, 1996) and, more specifically, because they constellate around the importance of inertia – that ‘steps in a particular direction induce further movement in the same direction’ (Pierson, 2000, p.252).…”
Section: Introductionmentioning
confidence: 99%
“…As Rubin (2023) notes, the complex and subtle mechanisms explored in path dependence scholarship are at times reduced to the notion of simple inertia – that policies remain the same merely because there are no incentives to change them. It may be tempting on the surface to explain prolonged de facto abolitions, of the type explored here, by such inertia.…”
Section: Conclusion: Stability Inertia and Intentionmentioning
confidence: 99%
“…Penal change has been perhaps the main topic of study in punishment and society scholarship (Rubin, 2023), and the death penalty is among the prime examples of this focus. Issues such as the decline in the use of the death penalty, the end of public executions, or processes of abolition, have featured in key classic and contemporary texts, from Durkheim to Foucault (1977) to Garland (2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation